Broadcast Spawning by Pocillopora Species on the Great Barrier Reef - Schmidt-Roach, Sebastian; Miller, Karen J.; Woolsey, Erika; Gerlach, Gabriele; Baird, Andrew H. (PLOS ONE, 2012)
The coral genus Pocillopora is one of the few to include some species that broadcast spawn gametes and some species that brood larvae, although reports of reproductive mode and timing vary within and among species across their range. Notably, the ubiquitous Pocillopora damicornis has been described as both a brooder and spawner, although evidence of broadcast spawning is rare. Here, we report observations of broadcast-spawning in four species of Pocillopora on the Great Barrier Reef (GBR), including P. damicornis. All species spawned predictably during the early morning, two days following the full moon, and spawning was observed in multiple months over the summer period (November to February). Eggs and sperm were free-spawned concurrently. Eggs were negatively buoyant and contained Symbiodinium. This newfound knowledge on the mode, timing and regularity of broadcast spawning in Pocillopora spp. on the GBR brings us one step closer to elucidating the complex reproductive ecology of these species.